Current Trends and Perspectives in the Application of Polymeric Materials for Wastewater Treatment - Otero, Marta; Coimbra, Ricardo N. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Water is indispensable to the functioning of most known life forms, and good water quality is essential to human health, social and economic development, and ecosystem functioning. Nonetheless, population growth has been leading to the degradation and depletion of fresh water resources. Under these circumstances, ensuring sufficient and safe water supplies for everyone is one of the Sustainable Development Goals (SDGs) set by the United Nations General Assembly in 2015 for the year 2030. For this goal to be achieved, the development and implementation of appropriate and efficient wastewater treatments that allow us to reduce water pollution is a major challenge.In view of the relevant contribution that polymers and polymeric materials may have in the conservation of the aquatic environment, namely by their application in wastewater treatment, original research and review papers on "Current trends and perspectives in the application of polymeric materials for wastewater treatment" were here brought together. For sure, this set of papers will be helpful and inspiring for readers interested in this topic.